Mechanisms of bacterial conversion and degradation of pharma pollutants from nonsteroidal anti-inflammatory drugs - Ivshina, I.B.; Tyumina, E.A.; Bazhutin, G.A.; Selyaninov, A.A.; Vikhareva, E.V. (Perm Federal Research Centre Journal, 2020)
Recently, there has been a steady increase in fundamental interest in studying the degree of bioavailability and toxic effects of pharmaceutical pollutants on natural microorganisms, which play the role of a primary response system to the xenobiotic load in the environment. Employing the bioresources of the Regional Specialised Collection of Alkanotrophic Microorganisms (IEGM, Large-Scale Research Facilities number 73559, WDCM # 768, http://www.iegmcol.ru), the ability of actinobacteria of the genus Rhodococcus to decompose complex aromatic compounds that constitute the non-steroidal anti-inflammatory drugs (NSAIDs) widely used for medical purposes was first established. Active biodegraders of diclofenac and ibuprofen, which dominate among NSAIDs detected in the natural environment and pose the greatest potential risk to hydrobiota and humans, were selected. The kinetics and main characteristics of the biodegradation process of the tested pharmaceutical pollutants were investigated depending on the physiological state and culture conditions of their biodegraders. Cytochrome P450-dependent monooxygenases were shown to participate in the initial oxidation of the pharma pollutants. The products of bacterial decomposition of the ecotoxicants were identified, the pathways of their biodegradation were characterized, and the mathematical models of the process of complete bacterial degradation of pharmaceutical pollutants in high concentrations were described. For the first time, evidence for the C-N bond breaking and aromatic ring opening in the diclofenac structure accompanied by the formation of metabolites harmless to living organisms was obtained. Potential bioactivity of individual metabolites of diclofenac and ibuprofen was evaluated. The most typical reactions of rhodococci exposed to NSAIDs were as follows: changes in the zeta potential, morphometric parameters and degree of hydrophobicity of bacterial cells, an increased content of total cellular lipids, and the formation of bacterial associates. The obtained results are considered to be mechanisms of rhodococci adaptation and their increased resistance to toxic effects of the pharmaceutical pollutants tested. The obtained fundamental data elucidate the environmental role of rhodococci in detoxification of pharma pollutants and underpin the implementation of innovative technical solutions for advanced pharmaceutical sewage treatment and the pharmaceutical waste disposal.